Multimodale Verkehrsmittelnutzer im Alltagsverkehr. Zukunftsperspektive für den ÖV? - Beckmann, Klaus J.; Chlond, Bastian; Kuhnimhof, Tobias; Ruhren, Stefan von der; Zumkeller, Dirk (Deutscher Verkehrs-Verl., 2006)
Untersuchungen zum Verkehrsmittelwahlverhalten und zur individuellen Verkehrsmittelverwendung zeigen, dass etwa die Hälfte der Auto fahrenden Bevölkerung auch Kunde des öffentlichen Verkehrs (ÖV) ist. Diese als "Multimodale" bezeichnete Verkehrsteilnehmergruppe wird voraussichtlich in Zukunft ein immer wichtigeres Kundensegment für den öffentlichen Verkehr. Ursache ist die u.a. demografisch bedingte Abnahme des Anteils der ÖV-gebundenen Bevölkerungsgruppen (Kinder, Jugendliche, nichtmotorisierte ältere Menschen), welche die derzeitige Stammkundschaft des ÖVs bilden. difu

Research carried out into behavioural aspects relating to the selection of means transport and personal preference has shown that about half of all car users also tend to be public transport customers. These so-called 'multimodal' travelers are likely to emerge as an increasingly important customer segment of the public transport sector. This is due to a future decrease in certain population groups' share in public transport for reasons related to demography, which includes children, young persons, and elderly people without a car, all of whom are habitual public transport users at present. Against this background and in support of public transport, efforts should focus on winning, and keeping, multimodal travelers. lt is absolutely essential to find out more about their reliance on, and selection of, means of transport. The article presents the results of a research project that deals with customers' behavioural pattern. difu
Keywords: Öffentlicher Verkehr; Verkehrsmittelwahl; Verkehrsverhalten; Mobilität; Verkehrsplanung; Verkehrsstatistik; Verkehrsnachfrage; ÖPNV; Stadtverkehr; Bevölkerungsstruktur; Altersstruktur; Perspektive; Individualverkehr; Kundenorientierung; Fahrradnutzung